Peran birokrasi dalam peningkatan mutu pendidikan di Indonesia - An-nuriyah, I'anatul Adhimah (Maliki Interdisciplinary Journal, 2024)
The role of bureaucracy in improving the quality of education in Indonesia. The role of bureaucracy is not only as a controller or supervisor, but also as a facilitator, motivator, and inspirer. Through a professional national education bureaucracy-building program, the bureaucracies strive to improve their ability and performance to the desired goals. The bureaucracy in education involves government officials, teachers, and students in the learning process as well as the development of quality education. The challenges faced by the role of bureaucracy in improving the quality of education include lack of socialization, less effective coordination, minimal involvement, lack of openness, and innovation in the management of education. To overcome these challenges, bureaucracies need to become more open, responsible, professional, participatory, innovative, creative, and adaptive in the face of change in today's globalized era. With a deep understanding of the role of bureaucracy, it is expected to create a more effective, efficient, and quality education system in Indonesia, so that people can well-being through superior education.